2011
DOI: 10.1007/s11103-011-9735-7
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of a rice aldo–keto reductase increases oxidative and heat stress tolerance by malondialdehyde and methylglyoxal detoxification

Abstract: The accumulation of toxic compounds generated by the interaction between reactive oxygen species and polyunsaturated fatty acids of membrane lipids can significantly damage plant cells. A plethora of enzymes act on these reactive carbonyls, reducing their toxicity. Based on the chromosomal localization and on their homology with other stress-induced aldo-keto reductases (AKRs) we have selected three rice AKR genes. The transcription level of OsAKR1 was greatly induced by abscisic acid and various stress treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 60 publications
(74 reference statements)
4
89
0
Order By: Relevance
“…Lipid peroxidation can be estimated as the amount of MDA present in plants as an effect of oxidative damage [18]. Overproduction of OsAKR1 protein in transgenic tobacco plants detected lower levels of MDA and methylglyoxal (MG) in leaf tissues subjected to chemical and heat stress treatments [4]. Based on these observations we can predict the potential role of AKRs in reactive carbonyls detoxification and promoting abiotic stress tolerance as a consequence.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Lipid peroxidation can be estimated as the amount of MDA present in plants as an effect of oxidative damage [18]. Overproduction of OsAKR1 protein in transgenic tobacco plants detected lower levels of MDA and methylglyoxal (MG) in leaf tissues subjected to chemical and heat stress treatments [4]. Based on these observations we can predict the potential role of AKRs in reactive carbonyls detoxification and promoting abiotic stress tolerance as a consequence.…”
Section: Introductionmentioning
confidence: 90%
“…Overproduction of an alfalfa AKR (MsALR) protein in transgenic tobacco plants improves tolerance against variety of oxidative stress induced by methylviologen (MV), heavy metals (CdCl 2 ), osmotic and long periods of drought [11], cold [12], UV radiation [13] compared to wild type plants. Heterologous overexpression of OsAKR1 in tobacco plants showed better tolerance against heat [4]. Overexpression of Arabidopsis AKR4C9 in transgenic barley showed enhanced freezing tolerance and higher post-frost regenerative capacity [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turóczy et al (2011) investigated two mechanisms how overexpression of ARKs in tobacco enhances high temperature tolerance. First, many AKRs are effective in the synthesis of osmolytes, thus having important role in the osmoregulation, which is an important process in plants for the acquisition of desiccation tolerance due to high temperature.…”
Section: High Temperature Tolerancementioning
confidence: 99%
“…Overexpression of the ALR gene in tobacco increases tolerance against oxidative agents and low temperature, Cd and drought stress (Oberschall et al, 2000;Hegedüs, 2004). Turóczy et al (2011) reported that transgenic plants overexpressing the OsAKR1 gene showed oxidative stress tolerance induced by methyl viologen (MV) and high temperature. The transgenic plants also exhibited higher AKR activity and accumulated less MG under heat stress conditions.…”
Section: Methylglyoxal (Mg) and Its Formation In Biological Systemmentioning
confidence: 99%